The Meaning of News in the Qur’an: An Analysis of the LPPIQ Surabaya Thematic Turjuman Book - Khairunnisa, Naura Maulika (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Arabic is one of the languages ​​with the largest vocabulary. Its richness of forms allows a single word to be applied in various different ways. One example is the word "news," which in the Quran has various forms that share a similar meaning space. This study aims to analyze the meaning field of the word "news" in the Quran, which has various forms. This study used a qualitative method with a semantic field analysis approach. The research data comes from the vocabulary of "news" in the Quran, compiled in the LPPIQ Surabaya thematic turjuman learning module. Preliminary results indicate that each word is interconnected and forms a structured meaning field. Each word contains different nuances of meaning, according to its use and the context of the verse. This diversity demonstrates the lexical richness of Arabic in describing something specifically and deeply.